Diseño de factibilidad para la creación de una empresa distribuidora de insumos agropecuarios con el servicio de ventas a domicilio en la zona central de Quevedo, año 2015. - Murillo Vallejo, Patricio Fernando (2016)
The present research on the "Design of feasibility for the creation of a distributor of agricultural inputs sales service delivery in the central area of Quevedo, 2015" has the main objective to analyze the current situation on the sale of agricultural inputs also verify farming with respect to the cantons surrounding the production and sale of agricultural products such as Valencia, Mocache, Buena Fe. For the development of research, through the conceptual and referential framework was based through specific variables, the necessary information about the theories of production, is presented also on the agricultural sector, the sale of agricultural inputs on the matrix productive, finishing with relevant articles that warrant investigation. The marketing of agricultural inputs in the cantons: Quevedo, Mocache, good faith and Windows are large because of the competition that exists today with 22 companies of agricultural inputs that sell products to small and medium farmers, but now the demand is unsatisfied customers do not receive the attention, the price of inputs and services are inadequate. It is necessary for companies that sell agricultural inputs, improve their service strategies, implementing greater efficiency in its business and regulating the sales prices of the input, with farmers beneficiaries improving crop production, while generating productivity and contributing to the change in the production matrix country. Keywords: business, supplies, agricultural, service, sales